Relationship between earnings management, CEO compensation, and stock return on Tehran Stock Exchange. Issue 1 (19th December 2019) - Moardi, Mahdi; Salehi, Mahdi; Poursasan, Simin; Molavi, Homa
Abstract : Purpose: The purpose of this paper is to investigate the relationship between earnings management and chief executive officers' (CEOs) compensation. Owing to the fact that earnings management does not have only opportunistic effects, but signaling effects, this study focuses on accruals quality to examine earnings management incentives. Thus, accruals quality is described against future cash flow. The empirical evidences suggest that a positive relationship between discretionary accruals and future cash flow provides predictive elements for earnings management, whereas a negative relationship between discretionary accruals and future cash implies to opportunistic elements for earnings management. Should there is no significant relationship between discretionary accruals and future cash flow, there will be no earnings management, and such a result suggests that incentives and managers' performance in these firms differ. Design/methodology/approach: The statistical population of this research consists of all listed companies on the Tehran Stock Exchange during 2009–2016. Panel data method is applied in order to estimate the research model. Findings: Findings of the study show that there is no significant relationship between discretionary accruals and future cash flow in pharmaceutical and food industries, thus they have neither predictive nor opportunist earnings management, while the results evidence a negative significant relationship between discretionary accruals and future cash flow in machineries, automobile, mineral and chemical industries. Furthermore, it can be alleged that there is no significant difference between CEOs' compensation in firms with opportunistic earnings management (OEM) and other types of earnings management. It shows that firms do not have appropriate plans for CEOs' compensation. Moreover, the relationship between earnings management and stock return has been investigated in this study. We document that stock return is influenced by accruals quality and its components. In other words, stock return significantly differs in firms with OEM and firms without any kind of earnings management. Research limitations/implications: The authors' findings provide contributions; for managers, it is noticeable that stock markets have sufficient comprehension about financial statements and the undertaken procedures on them, resulting in a higher return base on fair information. For investors and regulators, using the findings, may have deeper understanding to distinguish between industries that are recognized as opportunistic and non-opportunistic, which, in turn, results in better decision and regulation. Originality/value: Previous studies have been mostly investigated OEM, while the current study examines both signaling and opportunistic aspects of earnings management.